Thermomechanical properties of graphene: valence force field model approach - Lajevardipour, A.; Neek-Amal, M.; Peeters, F. M. (Iop Publishing Ltd, 2012)
Using the valence force field model of Perebeinos and Tersoff (2009 Phys. Rev. B 79 241409(R)), different energy modes of suspended graphene subjected to tensile or compressive strain are studied. By carrying out Monte Carlo simulations it is found that: (i) only for small strains (vertical bar epsilon vertical bar (sic) 0.02) is the total energy symmetrical in the strain, while it behaves completely differently beyond this threshold; (ii) the important energy contributions in stretching experiments are stretching, angle bending, an out-of-plane term, and a term that provides repulsion against pi-pi misalignment; (iii) in compressing experiments the two latter terms increase rapidly, and beyond the buckling transition stretching and bending energies are found to be constant; (iv) from stretching-compressing simulations we calculated the Young's modulus at room temperature 350 +/- 3.15 N m(-1), which is in good agreement with experimental results (340 +/- 50 N m(-1)) and with ab initio results (322-353) N m(-1); (v) molar heat capacity is estimated to be 24.64 J mol(-1) K-1 which is comparable with the Dulong-Petit value, i. e. 24.94 J mol(-1) K-1, and is almost independent of the strain; (vi) nonlinear scaling properties are obtained from height-height correlations at finite temperature; (vii) the used valence force field model results in a temperature independent bending modulus for graphene, and (viii) the Gruneisen parameter is estimated to be 0.64.
Keywords: Suspended Graphene; Hydrocarbons; Monolayer; Graphite